Novel silicon bipodal cylinders with controlled resonances and their use as beam steering metasurfaces - Samar M. Fawzy (Nature Portfolio, 2021)
Abstract Metasurfaces have paved the way for high performance wavefront shaping and beam steering applications. Phase-gradient metasurfaces (PGM) are of high importance owing to the powerful and relatively systematic tool they offer for manipulating electromagnetic wave fronts and achieving various functionalities. Herein, we numerically present a novel unit cell known as bipodal cylinders (BPC), made of Silicon (Si) and placed on a Silicon dioxide (SiO2) substrate to be compatible with CMOS fabrication techniques and to avoid field leakage into a high index substrate. Owing to its geometrical structure, the BPC structure provides a promising unit cell for electromagnetic wave manipulation. We show that BPC offers a way to shift the electric dipole mode to a frequency higher than that of the magnetic dipole mode. We investigate the effect of varying different geometrical parameters on the performance of such unit cell. Building on that, a metasurface is then presented that can achieve efficient electromagnetic beam steering with high transmission of 0.84 and steering angle of 15.2°; with very good agreement with the theoretically predicted angle covering the whole phase range from 0 to 2 $$π$$ π .